THE CORRELATION BETWEEN STUDENTS’ PERCEPTION ON GERAKAN LITERASI SEKOLAH AND STUDENTS’ READING ENGLISH ACHIEVEMENT OF SMAN 4 KEDIRI - Fadhila, Madarina; Putri, Kristanti Yuntoro; Asyhar, Wildan Isna (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
This research aims to describe and analyze: (1) to find out students’ perception of the program Gerakan Literasi Sekolah, (2) to find out the reading English achievement of students’, (3) to find out the correlation between Gerakan Literasi Sekolah and students’ reading English achievement at SMAN 4 Kediri. This research used the quantitative approach as the research design. Then, the data collected by using questionnaire and document. This research carried out 194 students of eleventh grade of SMAN 4 Kediri as the sample. The result showed that: (1) the results of the students' perceptions of the Gerakan Literasi Sekolah took a sample of 194 students. The questionnaire consists of 20 questions, with a total of 3.880 answers. Data analysis of the average number of students answered